Al Hafiy Design / Muhammad Ashraf Mohamad Diah ... [et al.] - Mohamad Diah, Muhammad Ashraf; Jamiluddin, Muhammad Fakhrur Razi Al Hafiy; Jasmin, Affiz Jazimin; Che Daud, Ahmad Izham (2021)
Nowadays, the industry of clothing have been increasing very well. The evolution of fashion on the clothing industry have becoming more advance and varied as many years goes by. This evolution also includes the advancement on the industry of sport shirt. This is what Al Hafiy Design are dedicated to, where we are focused on providing the best quality of sport shirt production to our customer while at the same time offering an affordable price. We are committed to provide the best services and products in this business industry to our customer by practicing a suitable and preferable policy in our business operation and activities in order to fulfil their satisfaction and needs. In our business service, we provide our customer with a high quality, customizable and easy to purchase method for our customer. As we already know that there is a lot of competitor in this business industry, we also try our best to provide a better service and product which is have its own difference compared to them. We also have our own uniqueness in our product which we provide a service of customizable printing for our sport shirt. With this, customer are able to design their own shirt that they want to buy according to their own preference. This service are provided in order to gives more satisfaction and fulfil our customer dream shirt where they are able to wear the shirt that they design according to their own style and likes. Also, we can gives a consultation to our customer for each of the shirt that they want to customize on what is the most suitable and best material can be used. Al Hafiy Design are already aware of the rise of online shopping and e-commerce in this business industry. Because of that, we have create a numbers of our business group on the social media application such as Whatsapp, Facebook, Instagram and Twitter. We know that most of people today are already familiar and always use social media in their daily life routine for many purpose and reason. Because of that, we want to provide a platform that is most convenient for our customer to get the information and news on our product and services with the preferred way by them. This is how we show our determination in order to provide our product and services with a friendly method, but at the same time effective. We also will always improve and updating our method of business activity from time to time to make sure that Al Hafiy Design will always remain competitive in this business industry.